THE EFFECT OF COLLABORATIVE PROJECT PLAY CRAFTING ON THE SOCIAL INTERACTION SKILLS OF CHILDREN WITH AUTISM IN THE ATHIRAH MAKASSAR INCLUSIVE ELEMENTARY SCHOOL - Kiki Risky Nanda; Abdul Saman; Parwoto Parwoto (Jurnal Konseling Pendidikan Islam, 2026)
This research aims to develop a valid, reliable, and practical Google Forms-based The Influence of Collaborative Project Play Crafting on the Social Interaction Skills of Children with Autism at Athirah Makassar Inclusive Elementary School. Thesis. Guidance and Counseling Study Program. Graduate Program. Universitas Negeri Makassar (supervised by Abdul Saman and Parwoto). This study aims to determine: (1) the effect of collaborative project play crafting on the social interaction skills of autistic children in inclusive elementary schools, and (2) the changes in the social interaction skills of autistic children before and after participating in the collaborative project play crafting activities. This research uses a quantitative approach with the Single Subject Research (SSR) design A-B-A method. Data collection techniques were carried out through direct observation and portfolio studies, with instruments developed based on the Social Skills Rating System (SSRS) indicators. The data were analyzed using descriptive statistics, both within conditions and between conditions. The results of the study show that: (1) collaborative project play crafting has a significant effect on improving the social interaction skills of autistic children. This is evidenced by the increase in scores during the intervention phase (B) compared to the initial baseline phase (A1), as well as the stability of scores in the final baseline phase (A2), indicating that the intervention effect is lasting; (2) there were significant changes between baseline condition A1, intervention B, and baseline A2. In Baseline A1, children displayed low social skills (average scores of 2.0–2.5), but this increased to 3.5–3.8, in baseline A2, particularly in the areas of cooperation, social initiative, and responses to social stimuli. Therefore, this intervention is effective in improving the social interaction skills of autistic children in an inclusive educational environment.